Risk factors of postoperative hydrocephalus following decompressive craniectomy for spontaneous intracranial hemorrhages and intraventricular hemorrhage. Issue 41 (14th October 2022) - Wu, Yi-Chieh; Liao, Hsiang-Chih; Lin, Jang-Chun; Chou, Yu-Ching; Ju, Da-Tong; Hueng, Dueng-Yuan; Tang, Chi-Tun; Tseng, Kuan-Yin; Chou, Kuan-Nien; Lin, Bon-Jour; Feng, Shao-Wei; Chen, Yi- An; et al.
Abstract : Introduction: Hydrocephalus is a complication of spontaneous intracerebral hemorrhage; however, its predictive relationship with hydrocephalus in this patient cohort is not understood. Here, we evaluated the incidence and risk factors of hydrocephalus after craniectomy. Methods: Retrospectively studied data from 39 patients in the same hospital from 2016/01 to 2020/12 and analyzed risk factors for hydrocephalus. The clinical data recorded included patient age, sex, timing of surgery, initial Glasgow Coma Scale score, intracerebral hemorrhage (ICH) score, alcohol consumption, cigarette smoking, medical comorbidity, and blood data. Predictors of patient outcomes were determined using Student t test, chi-square test, and logistic regression. Results: We recruited 39 patients with cerebral herniation who underwent craniectomy for spontaneous supratentorial hemorrhage. Persistent hydrocephalus was observed in 17 patients. The development of hydrocephalus was significantly associated with the timing of operation, cigarette smoking, and alcohol consumption according to the Student t test and chi-square test. Univariate and multivariate analyses suggested that postoperative hydrocephalus was significantly associated with the timing of surgery ( P  = .031) and cigarette smoking ( P  = .041). Discussion: The incidence of hydrocephalus in patients who underwent delayed operation (more than 4 hours) was lower than that in patients who underwent an operation after less than 4 hours. nonsmoking groups also have lower incidence of hydrocephalus. Among patients who suffered from spontaneous supratentorial hemorrhage and need to receive emergent craniectomy, physicians should be reminded that postoperative hydrocephalus followed by ventriculoperitoneal shunting may be necessary in the future.